Transformative mechanisms in decarbonization policies: A structured approach - Sousa, C.; Fontes, M.; Bento, N. (18th IAEE European Conference, 2023)
The transition to a low-carbon society should accelerate to avoid an increase in the temperatures above 1.5º to 2ºC, and this is unlikely to occur without policy intervention (IPCC, 2022). Given the complexity of the problem, recent debates have increasingly pointed to the need of adopting a new, broader view on policy intervention (Weber and Rohracher, 2012; Hekkert et al., 2020). This entails a move beyond a single focus on economic competitiveness and growth and towards a focus on societal problems or “grand challenges”, leading to the emergence of the concept of transformative innovation policy (Schot and Steinmueller 2018; Dierks et al., 2019). This new rationale implies the consideration of a much broader range of policy objectives, targets and instruments, as well as the notion that a mix of policies needs to be deployed to achieve the desired goals (Rogge and Reichardt, 2016).